Modulation of Type-I Interferon Response by hsa-miR-374b-5p During Japanese Encephalitis Virus Infection in Human Microglial Cells - Rastogi, Meghana; Singh, Sunit K. (Frontiers in Cellular and Infection Microbiology, 2019)
Japanese Encephalitis virus (JEV) is a neurotropic, ssRNA virus, belongs to Flaviviridae family. JEV is one of the leading causes of the viral encephalitis in Southeast-Asian countries. JEV primarily infects neurons however, the microglial activation has been reported to further enhance the neuroinflammation and promote neuronal death. The PI3K/AKT pathway has been reported to play an important role in type-I interferon response via IRF3. Phosphatase and tensin homolog (PTEN), a negative regulator of PI3K/AKT pathway participates in microglial polarization and neuroinflammation. The microRNAs are small non-coding endogenously expressed RNAs; which regulate the gene expression by binding at 3’UTR of target gene. The human microglial cells were infected with JEV (JaOArS982 strain) and up-regulation of microRNA; hsa-miR-374b-5p was confirmed by qRT-PCR. The genes in PI3K/AKT pathway, over-expression and knock-down studies of hsa-miR-374b-5p with and without JEV infection were analyzed through immuno blotting. The regulatory role of hsa-miR-374b-5p on the expression of type-I interferon was determined by luciferase assays. JEV infection modulated the expression of hsa-miR-374b-5p and PI3K/AKT pathway via PTEN. The over-expression of hsa-miR-374b-5p suppressed the PTEN while up-regulated the AKT and IRF3 proteins, whereas, the knockdown rescued the PTEN expression and suppressed the AKT and IRF3 proteins. The modulation of hsa-miR-374b-5p regulated the type-I interferon response during JEV infection. In present study we have shown the modulation of PTEN by hsa-miR-374b-5p, which regulated the PI3K/AKT/IRF3 axis in JEV infected microglial cells.